The Influence of Birth Ball Exercise and Lemon Aromatherapy on Cortisol Levels in Pregnant Women - Wenny Indah Purnama Eka Sari; Kurniyati; Yusniarita; Ida Mardalena (Postgraduate, University of Mataram, 2026)
Pregnancy is a natural and physiological condition. During pregnancy, various changes occur in the body due to the hormones estrogen and progesterone, which affect both the physical and psychological conditions of the mother. Anxiety during pregnancy is an emotional reaction related to the mother's concerns about her baby. Persistent anxiety can affect the sympathetic nervous system and the release of the stress hormone cortisol. The purpose of this study is to examine the effect of birth ball exercise and lemon aromatherapy on cortisol levels in pregnant women. This study employed a posttest-only control group approach in a quasi-experimental design. Thirty third-trimester pregnant women who engaged in pregnancy exercises made up the study sample; they were chosen using purposive sampling. For four weeks, the respondents in the intervention group received the lemon aromatherapy and birth ball exercise twice a week for forty-five minutes each. A questionnaire with respondent characteristics and a cortisol level column were part of the research tool. The non-parametric Mann-Whitney test was used for data analysis. The average cortisol levels in the intervention group and the control group differed significantly, as indicated by the results, which showed p = 0.000. This indicates that cortisol levels in third-trimester pregnant women are considerably impacted by lemon aromatherapy and birth ball exercise. cortisol levels are lowered by the physiological and psychological effects of the birth ball exercise and lemon aromatherapy, which relax the body and calm the mind. Pregnant women may benefit from combining lemon aromatherapy with birth ball exercise to lower anxiety levels and avoid excessive cortisol elevation.